Fluid Balance Management Informs Renal Replacement Therapy Use During Pediatric Extracorporeal Membrane Oxygenation: A Survey Report From the Kidney Intervention During Extracorporeal Membrane Oxygenation Group. Issue 3 (10th May 2021) - Gorga, Stephen M.; Lima, Lisa; Askenazi, David J.; Bridges, Brian C.; Cooper, David S.; Paden, Matthew L.; Zappitelli, Michael; Gist, Katja M.; Gien, Jason; Jetton, Jennifer G.; Murphy, Heidi J.; Fleming, Geoffrey M.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Fluid overload (FO) and acute kidney injury (AKI) occur commonly in children supported with extracorporeal membrane oxygenation (ECMO). Continuous renal replacement therapy (CRRT) may be used to manage AKI and FO in children on ECMO. In 2012, our group surveyed ECMO centers to begin to understand the practice patterns around CRRT and ECMO. Since then, more centers are initiating ECMO for increasingly diverse indications and an increased volume of research quantifies the detrimental impacts of AKI and FO. We, therefore, investigated practice patterns of CRRT utilization during ECMO in children. A multi-point survey instrument was distributed to 116 international neonatal and pediatric ECMO centers. Sixty of 116 (51.7%) international neonatal and pediatric ECMO centers responded. All reports using CRRT on ECMO, compared with 75% from the 2012 survey. Eighty-five percent use CRRT to treat or prevent FO, an increased from 59%. The modality of CRRT therapy differed between in-line (slow continuous ultrafiltration, 84.4%) and machine-based (continuous venovenous hemodiafiltration, 87.3%) methods. Most (65%) do not have protocols for fluid management, AKI, or CRRT on ECMO. Trialing off CRRT is dictated by physician preference in 90% (54/60), with varying definitions of success. In this survey study, we found that CRRT use during pediatric ECMO has increased since 2012 with fluid management representing the predominant indication for initiation. Despite the expanded utilization of CRRT with ECMO, there remains significant practice variation in terms of method, modality, indication, the timing of initiation, fluid management, and discontinuation.